Immediate effects of acute Mars mission equivalent doses of SEP and GCR radiation on the murine gastrointestinal system-protective effects of curcumin-loaded nanolipoprotein particles (cNLPs) - Diaz, Jonathan; Kuhlman, Bradford M.; Edenhoffer, Nicholas P.; Evans, Angela C.; Martin, Kelly A.; Guida, Peter; Rusek, Adam; Atala, Anthony; Coleman, Matthew A.; Wilson, Paul F.; Almeida-Porada, Graça; Porada, Christopher D. (Frontiers in Astronomy and Space Sciences, 2023)
Missions beyond low-Earth orbit (LEO) will expose astronauts to ionizing radiation (IR) in the form of solar energetic particles (SEP) and galactic cosmic rays (GCR) including high atomic number and energy (HZE) nuclei. Unfortunately, the limited understanding of the biological effects of chronic low dose-rate exposures of charged particles and their secondary radiations present in the space radiation environment, as well as sporadic high dose/dose-rate solar particle events (SPEs), confounds risk assessments for planned exploratory missions to the Moon and Mars. The gastrointestinal (GI) system is documented to be highly radiosensitive with even relatively low dose IR exposures capable of inducing mucosal lesions and disrupting epithelial barrier function. IR is also an established risk factor for colorectal cancer (CRC) with several studies examining long-term GI effects of SEP/GCR exposure using tumor-prone APC mouse models. Studies of acute short-term effects of modeled space radiation exposures in wildtype mouse models are more limited and necessary to better define charged particle-induced GI pathologies and test novel medical countermeasures (MCMs) to promote astronaut safety. In this study, we performed ground-based studies where male and female C57BL/6J mice were exposed to -rays, 50 MeV protons, or 1 GeV/n Fe-56 ions at the NASA Space Radiation Laboratory (NSRL) with histology and immunohistochemistry endpoints measured in the first 24 h post-irradiation to define immediate SEP/GCR-induced GI alterations. Our data show that unlike matched -ray controls, acute exposures to protons and iron ions disrupts intestinal function and induces mucosal lesions, vascular congestion, epithelial barrier breakdown, and marked swelling of local lymph nodes. We also measured kinetics of DNA double-strand break (DSB) repair using gamma-H2AX-specific antibodies and apoptosis via TUNEL labeling, noting the induction and disappearance of extranuclear cytoplasmic DNA marked by gamma-H2AX only in the charged particle-irradiated samples. We show that 18 h pre-treatment with curcumin-loaded nanolipoprotein particles (cNLPs) delivered via IV injection reduces DSB-associated foci levels and apoptosis and restore crypt villi lengths. These data improve our understanding of physiological alterations in the GI tract immediately following exposures to modeled space radiations and demonstrates effectiveness of a promising space radiation MCM.